Revisiting the "July Effect" in Plastic Surgery: New Data to Support Resident Autonomy. Issue 1 (January 2020) - Coombs, Demetrius M.; Ascha, Mustafa S.; Ascha, Mona; Gatherwright, James; Knackstedt, Rebecca; Gurunluoglu, Raffi
Abstract : Background: The "July Effect" represents a topic of considerable interest across residency programs. This study investigated the frequency of postoperative complications following procedures with plastic surgery resident participation (all postgraduate year [PGY] levels) during the first (quarter 3, July–September) and last academic quarters. Methods: The American College of Surgeons National Surgical Quality Improvement Program database was used to calculate complication rates from 2006 to 2010. Resident involvement was analyzed as a categorical variable consisting of "juniors" (PGY1–PGY3), and "seniors" (PGY4–PGY6). Outcomes from procedures during Q3 were compared with all quarters. Propensity score matching and adjustment enabled logistic regression identifying the effect of resident involvement and admission. Results: Among all cosmetic and reconstructive procedures (n = 6625), mean operative time was not significantly greater in Q3 compared with all other quarters ( P = 0.069); no significant differences in complication rates were observed between Q3 and all other quarters, though superficial surgical site infection (SSI) approached significance (3.3% of procedures in Q3 vs 2.5% in all other quarters, P = 0.063). Among reconstructive procedures only (n = 5677), mean operative time was not significantly greater in Q3 compared with all other quarters ( P = 0.119); the same held true for cosmetic procedures only ( P = 0.275). Surgical site infection, however, was significantly more likely to occur with reconstructive procedures only, in Q3 compared with all other quarters (3.5% of cases vs 2.3%, P = 0.024). When adjusting for PGY status and matching populations, superficial SSI and return to the operating room were not significantly more common in Q3. When adjusting for quarter of admission, however, superficial SSI was significantly more common among the overall and noncosmetic cases with participation by junior residents ( P = 0.013 and 0.020, respectively). Conclusions: This may represent the first fully reproducible, transparent National Surgical Quality Improvement Program study in plastic surgery that demonstrates the absence of a clinically significant "July Effect, " and suggests that an appropriate degree of resident autonomy may pose minimal risk during both cosmetic and reconstructive procedures in residency training. Additionally, the findings encourage the development a plastic surgery-specific database to remedy inherent difficulties with larger, more comprehensive surgical databases.